PENANGANAN GANGGUAN PESAWAT TELEPON PADA JARINGAN VCCS DI PERUM LPPNPI CABANG PALEMBANG BANDAR UDARA INTERNASIONAL SULTAN MAHMUD BADARUDDIN II - Praja, Havan Hak (Journal of Engineering and Transportation, 2024)
On the Job Traning is a self-development activity carried out by the Indonesian Aviation Polytechnic Curug to develop the skills and understanding of cadets with what has been learned during their education at the Indonesian Aviation Polytechnic Curug campus.OJT is a means to apply the theories and practices that have been learned at the PPI Curug campus which are useful for adding insight, knowledge, experience, and real pictures as technicians who work in teams so that problems are repaired and equipmentworks as its function.the implementation of OJT is carried out by cadets in accordance with their respective fields to produce technicians who are experts, especially in their fields such as aviation telecommunications. One of the aviation telecommunication tools is the Voice Control Communication System which functions to coordinate the entire communication network used by ATC by switching radio voice channels and telephone voices automatically based on radio frequency addresses or telephone numbers displayed on the touch screen panel that is interconnected via VoIP making it easier for ATC to communicate both radio and telephone to ATC, technician, as well as to the pilot.